2008
DOI: 10.1093/humrep/den411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual cycle on circulating endothelial progenitor cells

Abstract: CD133(+)CD34(+)KDR(+) cells but not CFU-EPCs vary during the menstrual cycle. Our findings suggest a potential role for circulating EPCs in the normal cycle of physiological angiogenesis and repair of the uterine endometrium that is independent of circulating sex steroids or inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…As previously described [9,20,21], 5 · 10 6 unmodified MNCs were resuspended in EndoCult Liquid Medium (Stem Cell Technologies) and plated on fibronectin-coated six-well plates (Becton Dickinson) for 2 days. The non-adherent cells were recovered, resuspended in fresh medium, and transferred to a fibronectin-coated 24-well plate (Becton Dickinson) at 1 · 10 6 per well in the presence or absence of G-CSF (100 ng mL ) for a further 3 days; the colonies per well were then counted, and the EPC frequency was calculated.…”
Section: Cfu-epcsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described [9,20,21], 5 · 10 6 unmodified MNCs were resuspended in EndoCult Liquid Medium (Stem Cell Technologies) and plated on fibronectin-coated six-well plates (Becton Dickinson) for 2 days. The non-adherent cells were recovered, resuspended in fresh medium, and transferred to a fibronectin-coated 24-well plate (Becton Dickinson) at 1 · 10 6 per well in the presence or absence of G-CSF (100 ng mL ) for a further 3 days; the colonies per well were then counted, and the EPC frequency was calculated.…”
Section: Cfu-epcsmentioning
confidence: 99%
“…True EPCs are defined as cells that, in culture over 3-4 weeks on collagen, can give rise to endothelial outgrowth cells (EOCs) [14][15][16], whereas cells that give rise over 5-6 days to colonies on fibronectin (colony-forming unit endothelial progenitor cells) (CFU-EPCs), formerly proposed to be EPCs [17], are now recognized to be generated by monocytes [16,18,19]. CFUEPCs stain for many endothelial markers [20,21] but also retain CD14 expression [22]. Monocytes can themselves mimic endothelial cells (ECs) by upregulating expression of many markers held to be endothelial, and have probably been mistaken for ECs in many investigations [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, E 2 increases the number of circulating EPCs and enhances their adherence and homing to the region of vascular damage. Likewise, in premenopausal women the number of circulating EPCs is synchronized with the menstrual cycle and is highest during the fertile period [Robb et al 2009;Foresta et al 2008]. Furthermore, EPCs in men reportedly showed a lower adherence capacity than those in premenopausal women, an effect that was abolished by E 2 supplementation [Fadini et al 2008].…”
Section: Senescent Bone Marrow-derived Epcs and Impairment Of Cardiovmentioning
confidence: 99%
“…Studies have demonstrated that EPC levels vary with age, gender, smoking and certain conditions such as diabetes, hypertension and/or other cardiovascular diseases. Robb et al demonstrated that EPC levels even vary during the menstrual cycle in a potential effort to repair the uterine endometrium 33 . Thus, studies involving measurement of EPC are affected by high individual variability, and study design should aim to reduce this by taking into account the variables described below.…”
Section: Why Do Epc Numbers Differ Among Studies Involving Copd Patiementioning
confidence: 99%